KEBUTUHAN PERAWATAN GIGI PADA ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA TAMAN PENDIDIKAN ISLAM MEDAN - Essie Octiara; Siti Salmiah; Zulfi Amalia; Luthfiani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Children with Special Needs is a person who has behavioral, physical and intellectual barriers that make doctor have to change approach with various ways to do the treatment. Children with special needs is a high-risk group for health problems, especially dental caries and periodontal disease, but in fact they are often too late to get dental treatment or never get the treatment. The purpose of this study was to determine the prevalence and experience of caries and dental care needs in children with special needs atSLB Taman Pendidikan Islam in Medan. The research was conducted by descriptive survey. The sample was 96 children with special needs with aged between 5-29 years old. Clinical caries examination using def-t / DMF-T (WHO) index and modified Treatment Need Index (TNI). The study is represent that the prevalence of children's caries is 92,71%. Experience of dental caries is 2,28+3,25; while the permanent dental caries experience was 3,02+2,98. Based on Treatment Need Index (TNI), the level of dental care needs was 656 teeth or average dental treatment of each child requires was 6.83 teeth, with the three most needed treatment is a surface restoration was 2.49 teeth, followed by tooth extraction was1.43 teeth and pulp treatment was 0.70 teeth. From the study it can be concluded that the level of dental hygiene in the chidren with special needs was still quite low, as well as the utilization of dental facilities.